Heavy Metal Concentrations in Three Commercial Fish Species in Cuddalore Coast, Tamil Nadu, India - Veerappan and T. Balasubramanian, P. Vijayakumar*, R. Lavanya, N. (Journal of Experimental Sciences, 2011)
Three fish species samples were collected from Cuddalore along Tamil Nadu coast, Bay of Bengal, India were analyzed for the levels of heavy metals to elucidate the status of the contamination in fish meat for human consumption. Concentrations of Cu, Cr, Cd, Co, Ni and Zn were determined for the above species using Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES). The concentrations of heavy metal in the samples were below the maximum residual level recommended by various organizations. Therefore, the fish muscles of the samples analyzed were fit for human consumption in this region.